2020
DOI: 10.1111/tmi.13366
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in measles vaccination status between 2004 and 2014 among children aged 12–23 months in Bangladesh

Abstract: objective To assess the current measles vaccination status in Bangladesh, explain changing differentials in measles vaccination, and determine contexts that may improve measles vaccination coverage.methods Secondary data analysis of datasets (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) from the nationally representative Bangladesh Demographic and Health Surveys that followed stratified, multi-stage cluster sampling design conducted both in urban and rural contexts.results 5468 children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…This study demonstrated that children born in households with higher wealth quintiles have significantly higher chances of being immunized against DPT, Polio, and Measles than children born in the poorest wealth quintile households. Similar results have been found in other settings [3,28,29,33,[44][45][46]. Moreover, no significant association is observed for BCG vaccination after adjusting other variables in the model.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study demonstrated that children born in households with higher wealth quintiles have significantly higher chances of being immunized against DPT, Polio, and Measles than children born in the poorest wealth quintile households. Similar results have been found in other settings [3,28,29,33,[44][45][46]. Moreover, no significant association is observed for BCG vaccination after adjusting other variables in the model.…”
Section: Discussionsupporting
confidence: 88%
“…Our research has also revealed that, after adjusting other variables to the model, lower birth order (AOR 2.38; CI: 1.18, 4.82) is found as a significant factor to have more likely of receiving BCG vaccination compared to higher birth order (≥4) and this result is similar with others [28,44]. Children who lived in a household having media exposure have 1.5 times (AOR 1.49; CI: 1.0, 2.23) more likely to be immunized against DPT, and these findings are supported by the others [3,44,45]. The place of residence is a significant factor for receiving Polio vaccination, and the likelihood of receiving the measles vaccine is twice (AOR 2.03; CI: 1.23, 3.36) for non-Muslim compared to their Muslim counterpart.…”
Section: Discussionsupporting
confidence: 82%
“…Ideally, they can provide information aimed at raising awareness and promoting vaccine adherence, with articles containing engaging and inviting content for interaction, providing greater reach. Jahan et al (2020) describe similar results in Bangladesh.…”
Section: Theme 3: Social Media and Social Mobilization As Factors To ...supporting
confidence: 59%